Copper foil and preparation method and application thereof

By forming a conductive layer composed of PTC material and dopamine-modified carboxymethylcellulose-derived conductive carbon on the copper foil, the problem of insufficient conductivity in the short circuit situation of the existing copper foil is solved, and the dual effect of good conductivity at normal temperature and circuit cutting in abnormal conditions is achieved, thereby improving the safety of battery use.

CN119764459APending Publication Date: 2025-04-04DONGGUAN DONGYANG SOLAR SCI RES & DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411806890.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The conductivity of existing copper foils in the normal temperature range of the battery is comparable to that of the battery after a short circuit, resulting in low safety in the battery.

Method used

A copper foil is used, which includes a copper substrate and a conductive layer on at least one side surface. The conductive layer is composed of PTC material and a conductive agent. The conductive agent includes dopamine-modified carboxymethyl cellulose or its salt-derived conductive carbon. Combined with carbon-based conductive agents such as carbon black, a high-efficiency conductive network is formed.

Benefits of technology

Maintain good conductivity within the temperature range of normal use of the battery. After abnormal situations such as battery short circuit, the resistance of the copper foil will quickly increase until the circuit is cut off, thereby improving the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764459A_ABST
    Figure CN119764459A_ABST
Patent Text Reader

Abstract

The invention relates to a copper foil, and particularly discloses a copper foil as well as a preparation method and application thereof. The copper foil comprises a copper substrate and a conductive layer located on at least one side surface of the copper substrate, and the conductive layer comprises a PTC material and a conductive agent. The conductive agent comprises a first conductive agent, the first conductive agent comprises conductive carbon, and the conductive carbon is obtained by reacting any one or more of dopamine modified carboxymethyl cellulose or salt thereof. The copper foil has good conductivity in the normal use temperature interval of the battery, and the resistance of the copper foil quickly increases until the circuit is cut off after the battery temperature rises due to abnormal conditions such as short circuit of the battery, so that the use safety can also be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a copper foil, and in particular to a copper foil and a preparation method and application thereof. Background Art

[0002] In the manufacturing process of non-aqueous secondary batteries, in order to improve the battery's rate performance and the adhesion of the active material to the electrode, a layer of conductive material is first coated on the surface of the current collector, and then the active material is directly coated on the surface of the current collector with the conductive material when manufacturing the electrode.

[0003] After the conductive material is coated on the surface of the current collector, the interface resistance between the current collector and the active material of the electrode sheet will decrease sharply. Summary of the invention

[0004] In view of the defects or shortcomings of the prior art, the purpose of this application is to provide a copper foil and its preparation method and application. The copper foil has good conductivity within the temperature range of normal battery use. When the battery temperature rises due to abnormal conditions such as short circuit, the resistance of the copper foil increases rapidly until the circuit is cut off, thereby improving the safety of use.

[0005] The first aspect of the present application is to provide a copper foil, which includes a copper substrate and a conductive layer located on at least one side of the copper substrate, the conductive layer includes a PTC material and a conductive agent; the conductive agent includes a first conductive agent, the first conductive agent includes conductive carbon, and the conductive carbon is obtained by reacting any one or more of dopamine-modified carboxymethyl cellulose or its salt.

[0006] In some embodiments, the dopamine-modified carboxymethyl cellulose or its salt includes any one or more of dopamine-modified carboxymethyl cellulose, dopamine-modified carboxymethyl cellulose sodium, dopamine-modified carboxymethyl cellulose potassium, and dopamine-modified carboxymethyl cellulose lithium;

[0007] The dopamine-modified carboxymethyl cellulose or its salt has excellent adhesiveness and has good adhesion and bonding force to carbon-based conductive agents such as carbon black, graphite, carbon nanotubes, and graphene on the surface of copper foil.

[0008] In some embodiments, the dopamine-modified carboxymethyl cellulose or its salt satisfies any one or more of the following properties:

[0009] (1) The grafting rate of dopamine in dopamine-modified carboxymethyl cellulose or its salt is 20% to 30%;

[0010] (2) The average relative molecular weight of the dopamine-modified carboxymethyl cellulose or its salt is 30,000 to 50,000.

[0011] In some embodiments, the conductive carbon content in the conductive layer is 5% to 20% by mass.

[0012] In some embodiments, the conductive layer further comprises a second conductive agent, and the second conductive agent comprises any one or more of carbon black, graphite, carbon nanotubes, and graphene;

[0013] In some embodiments, the mass percentage of the second conductive agent in the conductive layer is 35% to 85%. (The mass of the conductive carbon formed by sintering the CMC modified by dopamine is about 35% to 45% of the original mass. Taking Example 1 as an example, the conductive carbon formed by sintering the CMC modified by dopamine is about 3.5*0.4=1.4. The mass of the PTC material and carbon black remains basically unchanged after sintering. The dispersant, co-solvent and solvent are volatilized. The total mass remaining after sintering is 3+6+1.4=10.4. The mass percentage of the conductive carbon is 1.4 / 10.4*100%=13.46%)

[0014] In some embodiments, the PTC material is obtained by reacting a main material, a first additive and a second additive;

[0015] The main material includes barium titanate;

[0016] The first additive includes any one or more of antimony trioxide, yttrium trioxide, and tantalum pentoxide;

[0017] The second additive includes any one or more of lanthanum oxide, zirconium titanate, strontium oxide, and barium stannate;

[0018] The mass of the first additive is less than or equal to 1% of the mass of the PTC material;

[0019] The mass of the second additive is less than or equal to 10% of the mass of the PTC material;

[0020] The mass percentage of the PTC material in the conductive layer is 10% to 55%.

[0021] The second aspect of the present application is to provide a slurry for making the above-mentioned conductive layer, comprising the following components:

[0022] The total number of parts by mass is 100, of which:

[0023] PTC raw materials: 1 to 6 parts;

[0024] Second conductive agent: 4 to 9 parts;

[0025] Binder: 2 to 5 parts;

[0026] Dispersant: 0.5 to 3 parts;

[0027] Solvent: 3-10 parts; the rest is deionized water;

[0028] The binder includes any one or more of dopamine-modified carboxymethyl cellulose or its salt.

[0029] The third aspect of the present application is to provide a method for preparing the copper foil according to the first aspect, comprising the following process:

[0030] Providing a slurry for preparing the conductive layer: adding 2 to 5 parts of a binder, 3 to 10 parts of a cosolvent and 0.5 to 3 parts of a dispersant into deionized water for a first dispersion, adding 1 to 6 parts of a PTC raw material into the slurry after the first dispersion for a second dispersion, adding 4 to 9 parts of a second conductive agent into the slurry after the second dispersion for a third dispersion, and then sand-milling, stirring and degassing to obtain a slurry;

[0031] The binder includes any one or more of dopamine-modified carboxymethyl cellulose or its salt;

[0032] Pre-treating the copper substrate;

[0033] Coating and drying: coating the slurry on at least one side of the pretreated copper substrate, and drying to obtain a copper foil sample;

[0034] Sintering: The copper foil sample is placed in a reducing atmosphere and sintered to obtain the copper foil.

[0035] In some embodiments, the sintering temperature is 650° C. to 950° C., and the sintering time is 1 h to 12 h;

[0036] The reducing atmosphere includes an alkane gas atmosphere.

[0037] In some embodiments, the rotation speed of the first dispersion is 200 rpm to 800 rpm, and the dispersion time is 30 min to 60 min;

[0038] The second dispersion speed is 1000 rpm to 1500 rpm, and the dispersion time is 1 h to 3 h;

[0039] The rotation speed of the third dispersion is 1000 rpm to 1500 rpm, and the dispersion time is 2 h to 4 h.

[0040] The fourth aspect of the present application is to provide a current collector for a battery, comprising the copper foil described in the first aspect or the copper foil prepared by the preparation method described in the third aspect.

[0041] Beneficial technical effects of this application:

[0042] The copper foil prepared in the present application has good conductivity within the temperature range of normal battery use. When the battery temperature rises due to abnormal conditions such as a short circuit, the resistance of the copper foil increases rapidly until the circuit is cut off, thereby improving the safety of use. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a schematic diagram of the structure of the copper foil provided in some embodiments of the present application.

[0044] Figure 2 This is a process flow chart of the preparation of the copper foil of this application;

[0045] The reference numerals in the accompanying drawings represent the following:

[0046] 100: copper foil; 110: copper substrate; 120: conductive layer.

[0047] Coordinate axis x direction: thickness direction or stacking direction of copper foil;

[0048] Coordinate axis y direction: length or width direction of copper foil. DETAILED DESCRIPTION

[0049] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0050] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0051] Unless expressly stated to the contrary, all ranges cited herein are inclusive.

[0052] The term "a" or "an" used in this application is used to describe the elements and components described in this application. This is done only for convenience and to provide a general sense of the scope of this application. This description should be understood to include one or at least one, and the singular also includes the plural, unless it is obvious that it is otherwise intended. "Multiple" means two or more.

[0053] The numbers in this application are approximate, regardless of whether the words "about" or "approximately" are used. The numerical values ​​of the numbers may vary by 1%, 2%, 5%, 7%, 8%, 10%, etc. Whenever a number with a value of N is disclosed, any number with a value of N+ / -1%, N+ / -2%, N+ / -3%, N+ / -5%, N+ / -7%, N+ / -8% or N+ / -10% will be explicitly disclosed, where "+ / -" means plus or minus, and the range between N-10% and N+10% is also disclosed.

[0054] The current collector is an important component of the positive and negative electrodes in the battery cell. As a structure or part for collecting current, its function is to carry the active materials of the positive and negative electrodes, and to collect the current generated by the chemical reaction of the active materials to form a larger current for external output, thereby completing the conversion process of chemical energy into electrical energy. The ideal current collector needs to meet the characteristics of high conductivity (facilitating electron transmission and thus improving the specific capacity and rate performance of lithium batteries), good chemical and electrochemical stability (no interaction with active materials, binders and electrolytes), good mechanical strength (preventing damage to the battery caused by deformation under external forces such as collisions), strong bonding strength (good compatibility and bonding with battery active materials), and low cost and easy availability (so that large-scale production can be achieved).

[0055] At present, copper foil is usually used as the current collector for the negative electrode of the battery. According to the production process, copper foil can be divided into rolled copper foil and electrolytic copper foil. The process flow of electrolytic copper foil is short and the width of the format is large, so the market share of electrolytic copper foil is getting higher and higher.

[0056] The existing copper foil includes a copper metal substrate and a carbon-coated copper foil: the copper metal substrate is surface-modified by using a functional coating to form an excellent two-dimensional or multi-dimensional conductive network structure.

[0057] The conductivity of existing copper foil within the temperature range of normal battery use is equivalent to the conductivity after the battery short circuits, which is not conducive to the safe use of the battery.

[0058] In order to solve the above technical problems, the present application provides a copper foil, which includes a copper substrate and a conductive layer located on at least one side of the surface of the copper substrate, the conductive layer includes a PTC material and a conductive agent; the conductive agent includes a first conductive agent, the first conductive agent includes conductive carbon, and the conductive carbon is obtained by reacting any one or more of dopamine-modified carboxymethyl cellulose or its salt.

[0059] like Figure 1 Schematically, the present application provides a copper foil 100, which includes a copper substrate 110 and a conductive layer 120 located on one side of the copper substrate 110. Figure 1 It is schematically shown that the conductive layer 120 is formed on one side of the copper substrate 110 . In practice, the conductive layer 120 may also be formed on the other opposite side. The conductive layer 120 protects the copper substrate 110 , which is beneficial to further improve the conductivity of the copper foil.

[0060] The PTC (Positive Temperature Coefficient) material in the conductive layer 120 of the present application belongs to thermistor material. This material forms many small microcrystalline structures at the microscopic level, and there will be a barrier effect at the interface of the grains, which prevents electrons from crossing the boundary and entering the adjacent area. However, this effect will make the barrier very small when the temperature is low due to the high dielectric constant and spontaneous polarization intensity enhancement on the grain boundary, and the electrons can flow freely. Therefore, when the temperature is low, the resistance of the PTC material is low and it is in a conductive state. When the temperature rises, the dielectric constant and polarization intensity of the grain boundary are greatly reduced, resulting in a significant increase in the barrier, and the resistance presented to the outside continues to increase and rapidly increases to a large value to cause a circuit breaker.

[0061] The conductive layer 120 of the present application contains PTC material, so that the copper foil has good conductivity within the temperature range of normal battery use. However, when an abnormal situation such as a short circuit occurs in the battery, causing the battery temperature to rise (the temperature inside the battery rises), the resistance of the copper foil increases rapidly until the circuit is cut off, which is beneficial to improving the safety of use.

[0062] The conductive carbon in the conductive layer 120 of the present application is obtained by any one or more reactions of dopamine-modified carboxymethyl cellulose or its salt.

[0063] The dopamine-modified carboxymethyl cellulose or its salt of the present application has the following structural formula:

[0064]

[0065] The "~~~~" in the above structural formula represents other repeated structural units. The carboxyl group in the above structural formula is negatively charged and can be combined with hydrogen ions or metal cations.

[0066] The dopamine-modified carboxymethyl cellulose or its salt in the present application generates conductive carbon after reaction, and the conductive carbon and the PTC material are beneficial to improving the conductivity of the copper foil within the temperature range of normal battery use.

[0067] The conductive agent in the present application refers to a substance with conductivity, which plays the role of collecting microcurrent on the copper foil to reduce the contact resistance between the components in the copper foil to accelerate the movement rate of electrons.

[0068] In some embodiments, the dopamine-modified carboxymethyl cellulose or its salt includes any one or more of dopamine-modified carboxymethyl cellulose, dopamine-modified carboxymethyl cellulose sodium, dopamine-modified carboxymethyl cellulose potassium, and dopamine-modified carboxymethyl cellulose lithium.

[0069] The present application discloses in these embodiments that in the above structural formula, the negatively charged carboxyl group is connected to a hydrogen ion, a sodium ion, a potassium ion or a lithium ion.

[0070] The dopamine-modified carboxymethyl cellulose or its salt has excellent adhesion before conversion, and has good adhesion and bonding to carbon-based conductive agents such as carbon black, graphite, carbon nanotubes, graphene, etc. on the surface of copper foil. It is subsequently converted to generate conductive carbon, which together with the PTC material is beneficial to improving the conductivity of the copper foil within the temperature range of normal battery use.

[0071] In some embodiments, the dopamine-modified carboxymethyl cellulose or its salt satisfies any one or more of the following properties:

[0072] (1) The grafting rate of dopamine in dopamine-modified carboxymethyl cellulose or its salt is 20% to 30%;

[0073] (2) The average relative molecular weight of the dopamine-modified carboxymethyl cellulose or its salt is 30,000 to 50,000.

[0074] The grafting rate in the present application refers to the ratio between the mass of dopamine grafted onto carboxymethyl cellulose or its salt and the total mass of dopamine input in the grafting polymerization reaction between dopamine and carboxymethyl cellulose or its salt.

[0075] In these embodiments, the present application discloses that the grafting rate of dopamine in dopamine-modified carboxymethyl cellulose or its salt is any one of 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any one of the values ​​satisfying any two of the above ranges.

[0076] The average relative molecular weight in this application refers to the average value of all molecular masses in a group of compounds.

[0077] The present application discloses in these examples that the average relative molecular weight of the dopamine-modified carboxymethyl cellulose or its salt is any one of 30,000, 35,000, 40,000, 45,000, 50,000 or any one of the values ​​within the range of any two of the above.

[0078] In some embodiments, the conductive carbon content in the conductive layer is 5% to 20% by weight.

[0079] In these embodiments, the present application discloses that the mass percentage content of the above-mentioned conductive carbon in the above-mentioned conductive layer is any one of 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or any one of the values ​​in any two of the above ranges.

[0080] In some embodiments, the conductive layer further comprises a second conductive agent, and the second conductive agent comprises any one or more of carbon black, graphite, carbon nanotubes, and graphene;

[0081] In some embodiments, the mass percentage of the second conductive agent in the conductive layer is 35% to 85%.

[0082] In these embodiments, the present application discloses that the mass percentage content of the above-mentioned second conductive agent in the above-mentioned conductive layer is any one of 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or any one of the ranges of any two of the above. The present application also adds a second conductive agent to the conductive layer, and the second conductive agent works synergistically with the above-mentioned first conductive agent to make the battery have better conductivity within the temperature range of normal use. The types of the second conductive agent in the present application include any conventional types in the art, and the present application only schematically lists several types here.

[0083] The carbon black of the present application is one of the industrial products, and its main component is carbon, and contains a small amount of elements such as oxygen, hydrogen and sulfur.

[0084] The graphite in this application is an allotrope of carbon, mainly artificial graphite. The preparation method of artificial graphite includes: providing raw materials, crushing and shaping → granulation → graphitization → surface roughening treatment to obtain artificial graphite material. The graphite and carbon black in this application are both point-shaped conductive agents.

[0085] The carbon nanotubes of the present application refer to carbon allotropes, which include one or more cylindrical layers of carbon atoms, wherein the carbon atoms are covalently bonded into a hexagonal tiling pattern (i.e., graphene sheets), which form a hollow tube structure with a diameter of up to a few hundred nanometers. Graphene here refers to a sp 2 A one-atom-thick flat sheet composed of bonded carbon atoms, where the carbon atoms are tightly stacked in a honeycomb lattice. Carbon nanotubes are one-dimensional tubular structure conductive agents with good electron mobility. Carbon nanotubes include any one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes. The single-walled carbon nanotubes of this application refer to a single cylindrical layer of carbon atoms, and the multi-walled carbon nanotubes of this application refer to two or more layers of carbon atoms connected by intermolecular forces, or a single layer of carbon atoms wound several times around a cylindrical hollow core.

[0086] The graphene of the present application is a kind of sp 2 A single-layer carbon nanomaterial composed of hybridized carbon atoms has a flaky structure and good electron mobility. Graphene is a flaky conductive agent.

[0087] The present application discloses in some embodiments that the second conductive agent includes any one or more of carbon black, graphite, carbon nanotubes and graphene, which increases the conductivity of the copper foil by forming a conductive network.

[0088] In some embodiments, the PTC material is obtained by reacting a main material, a first additive, and a second additive;

[0089] The main material includes barium titanate;

[0090] The first additive includes any one or more of antimony trioxide, yttrium trioxide, and tantalum pentoxide;

[0091] The second additive includes any one or more of lanthanum oxide, zirconium titanate, strontium oxide, and barium stannate;

[0092] The mass of the first additive is less than or equal to 1% of the mass of the PTC material;

[0093] The mass of the second additive is less than or equal to 10% of the mass of the PTC material;

[0094] Moreover, the masses of the additives and barium titanate remain basically unchanged before and after the reaction.

[0095] The mass percentage of the PTC material in the conductive layer is 10% to 55%.

[0096] The barium titanate of the present application has the chemical formula BaTiO3 and is a strong dielectric compound material with a high dielectric constant and low dielectric loss. The Curie temperature (magnetic transition point, which is a property of the material with a crystal structure itself) is about 120°C. In order to lower the Curie temperature of barium titanate, the present application chooses to add a first additive and a second additive to the barium titanate. After adding the two types of additives, the Curie temperature of the PTC material drops to about 70°C. Therefore, in the early stage of heating of the battery in abnormal conditions such as short circuit, the temperature-sensitive resistance of the PTC material will increase to block the circuit and improve the safety of use.

[0097] In the present application, the chemical formula of antimony trioxide is Sb2O3, the chemical formula of yttrium trioxide is Y2O3, and the chemical formula of tantalum pentoxide is Ta2O5.

[0098] In the present application, the chemical formula of lanthanum oxide is La2O3, the chemical formula of zirconium titanate is ZrTiO4, the chemical formula of strontium oxide is SrO, and the chemical formula of barium stannate is BaSnO3.

[0099] In these embodiments, the present application discloses that the mass of the first additive is any one of 1%, 0.9%, 0.8%, 0.7%, 0.6%, 0.5%, 0.4%, 0.3%, 0.2%, 0.1% of the mass of the above-mentioned PTC material, or any one of the values ​​in any two ranges mentioned above.

[0100] In these embodiments, the present application discloses that the mass of the second additive is any one of 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1% of the mass of the above-mentioned PTC material, or any one of the values ​​in any two ranges mentioned above.

[0101] In these embodiments, the present application discloses that the mass percentage content of the above-mentioned PTC material in the above-mentioned conductive layer is any one of 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or any one of the ranges of any two of the above.

[0102] The second aspect of the present application is to provide a slurry for making the above-mentioned conductive layer, comprising the following components:

[0103] The total number of parts by mass is 100, of which:

[0104] PTC raw materials: 1 to 6 parts;

[0105] Second conductive agent: 4 to 9 parts;

[0106] Binder: 2 to 5 parts;

[0107] Dispersant: 0.5 to 3 parts;

[0108] Solvent: 3-10 parts; the rest is deionized water;

[0109] The binder includes any one or more of dopamine-modified carboxymethyl cellulose or its salt.

[0110] The binder in the present application refers to a compound, polymer or mixture that forms a colloidal solution or a colloidal dispersion in a dispersion medium.

[0111] As described above, dopamine-modified carboxymethyl cellulose or its salt has the above-mentioned structure and properties. In the process of forming a conductive layer by the slurry, the slurry is coated on at least one side of the copper substrate. The dopamine-modified carboxymethyl cellulose or its salt is beneficial to increase the adhesion of the slurry to the surface of the copper substrate.

[0112] The second conductive agent and the PTC raw material of the present application are as described above, and will not be described in detail here.

[0113] The dispersant of the present application is a surfactant, and the molecules of the dispersant have both lipophilic and hydrophilic properties, which is beneficial to improving the uniformity and stability of the dispersed substance in the solvent.

[0114] The present application discloses in these embodiments that the dispersant includes any one or more of BYK22092, BYK22136, and BYK22116. BYK22092, BYK22136, and BYK22116 refer to BYK-type wetting dispersants, and other types or types of dispersants are not excluded.

[0115] The solubility enhancer in the solvent is an additive that increases the solubility of a substance in a solvent.

[0116] The present application discloses in these embodiments that the co-solvent includes any one or more of ethanol, ethylene glycol, and isopropanol.

[0117] The dispersant and co-solvent of the present application are beneficial to the dispersion and dissolution of materials in the process of preparing the slurry. During the calcination process of forming the conductive layer, these components are volatilized from the conductive layer, so when calculating the content of each component of the conductive layer, these components are negligible.

[0118] The third aspect of the present application is to provide a method for preparing the copper foil according to the first aspect, comprising the following process:

[0119] Providing a slurry for preparing the conductive layer: adding 2 to 5 parts of a binder, 3 to 10 parts of a cosolvent and 0.5 to 3 parts of a dispersant into deionized water for a first dispersion, adding 1 to 6 parts of a PTC raw material into the slurry after the first dispersion for a second dispersion, adding 4 to 9 parts of a second conductive agent into the slurry after the second dispersion for a third dispersion, and then sand-milling, stirring and degassing to obtain a slurry;

[0120] The binder includes any one or more of dopamine-modified carboxymethyl cellulose or its salt;

[0121] Pre-treating the copper substrate;

[0122] Coating and drying: coating the slurry on at least one side of the pretreated copper substrate, and drying to obtain a copper foil sample;

[0123] Sintering: The copper foil sample is placed in a reducing atmosphere and sintered to obtain the copper foil.

[0124] like Figure 2 Schematically, a process flow chart of the above copper foil preparation method is provided.

[0125] In some embodiments, the sintering temperature is 650° C. to 950° C., and the sintering time is 1 h to 12 h;

[0126] The reducing atmosphere includes an alkane gas atmosphere.

[0127] During the sintering process of the present application, dopamine-modified carboxymethyl cellulose or its salt, which originally acts as a binder in the slurry, is converted into conductive carbon. The conductive carbon is sintered together with the PTC material and has good conductivity within the temperature range of normal battery use. When the battery has an abnormal situation such as a short circuit, the resistance of the copper foil increases rapidly until the circuit is cut off.

[0128] The sintering temperature and sintering time provided in this application are suitable to complete the above transformation.

[0129] The alkane gas atmosphere of the present application includes methane, ethane or propane, etc., which is beneficial to reduce the probability of oxidation of the copper substrate in the reducing atmosphere.

[0130] In these embodiments, the present application discloses that the sintering temperature is any one of 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or any one of the ranges of any two of the above.

[0131] In these embodiments, the present application discloses that the sintering time is any one of 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, and 12h, or any one of the ranges of any two of the above.

[0132] In some embodiments, the dispersion is performed using a disperser;

[0133] The rotation speed of the first dispersion is 200 rpm to 800 rpm, and the dispersion time is 30 min to 60 min;

[0134] The second dispersion speed is 1000 rpm to 1500 rpm, and the dispersion time is 1 h to 3 h;

[0135] The rotation speed of the third dispersion is 1000 rpm to 1500 rpm, and the dispersion time is 2 h to 4 h.

[0136] In some embodiments, the sand milling is performed in a horizontal sand mill, the rotation speed of the horizontal sand mill is controlled to be 1500 rpm to 2200 rpm, and the sand milling time is 1 h to 3 h.

[0137] In some embodiments, the above-mentioned method of pre-treating the copper substrate includes performing surface treatments such as corona, pickling or alkali washing on the copper substrate, and the corona, pickling or alkali washing methods include any conventional methods or processes or parameters in the art, which are not limited or elaborated in this application. The copper substrate described in this application is any copper substrate in the art, and is further selected as an electrolytic copper substrate.

[0138] In some embodiments, the drying comprises placing the pretreated copper substrate in an oven at 70° C. to 130° C. for drying for 1 min to 10 min.

[0139] In some embodiments, the thickness of the pretreated copper substrate is 3 μm to 10 μm.

[0140] In these embodiments, the present application discloses that the thickness of the pretreated copper substrate is any one of 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm, or any one of the values ​​within any two ranges above.

[0141] In some embodiments, the thickness of the conductive layer formed after the sintering is 0.4 μm to 1.2 μm.

[0142] The present application discloses in these embodiments that the thickness of the conductive layer formed after sintering is any one of 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm or any one of the values ​​in any two ranges above.

[0143] The present application also includes forming other functional coatings on the surface of the conductive layer away from the metal substrate, which will not be described in detail in the present application.

[0144] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0145] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0146] Conventional techniques of inorganic chemistry within the art can be used in this application. In the following examples, efforts are made to ensure the accuracy of the numbers used (including amounts, temperatures, reaction times, etc.), but some experimental errors and deviations should be considered. The temperatures (in degrees Celsius) used in the following examples are expressed in ° C, and the pressure is atmospheric pressure or near atmospheric pressure. All pharmaceutical reagents are purchased at AR grade, and all reactions are carried out under argon protection. Unless otherwise noted, all reagents are obtained from commercial channels.

[0147] raw material:

[0148] Barium titanate: commercially available;

[0149] Yttrium trioxide: commercially available;

[0150] Tantalum pentoxide: commercially available;

[0151] Antimony trioxide: commercially available;

[0152] Lanthanum oxide: commercially available;

[0153] Strontium oxide: commercially available;

[0154] Zirconium titanate: commercially available;

[0155] Barium stannate: commercially available;

[0156] Dopamine-modified sodium carboxymethyl cellulose: commercially available, in which the dopamine grafting rate is 25.2% and the average relative molecular weight is 36,000;

[0157] Dopamine-modified lithium carboxymethyl cellulose: commercially available, with a dopamine grafting rate of 22.9% and an average relative molecular weight of 32,000;

[0158] Dispersant: Commercially available;

[0159] Carbon black: commercially available;

[0160] Graphite: commercially available;

[0161] Copper substrate: commercially available.

[0162] Example 1

[0163] The preparation method of copper foil includes the following steps:

[0164] The mass fractions of the slurry are as follows:

[0165] Calculated by mass, the total number of parts is 100, including:

[0166] PTC raw materials (barium titanate 89.6%, antimony trioxide 0.4%, zirconium titanate 10%): 3 parts;

[0167] Conductive carbon black SP: 6 parts;

[0168] Dopamine-modified sodium carboxymethyl cellulose: 3.5 parts;

[0169] Dispersant (BYK22092): 2 parts;

[0170] Cosolvent (isopropanol): 5 parts;

[0171] Solvent (deionized water): Remaining parts: 80.5 parts.

[0172] S100, providing a slurry for making the above-mentioned conductive layer: adding a binder (dopamine-modified sodium carboxymethyl cellulose), a co-solvent (isopropyl alcohol), and a dispersant (BYK22092) to a solvent (deionized water) for high-speed dispersion for 30 minutes at a rotation speed of 500 rpm, then adding a PTC raw material, dispersing at high speed for 1 hour at a rotation speed of 1200 rpm, and finally adding a second conductive agent (conductive carbon black SP), dispersing at high speed for 3 hours at a rotation speed of 1200 rpm, discharging the material, placing the slurry in a horizontal sand mill, sand milling at 1800 rpm for 3 hours, then discharging the material, and stirring at a low speed for degassing to prepare a carbon layer slurry.

[0173] S200, pre-treating the copper substrate: performing corona treatment on the copper substrate;

[0174] S300, coating and drying: coating the slurry on one side of the pretreated copper substrate (thickness of 5 μm), with a single-side coating thickness of 5 μm; then placing the copper foil coated with the slurry in an oven at 100° C. for drying for 3 minutes to obtain a copper foil sample;

[0175] S400, sintering: placing the copper foil sample in a methane gas atmosphere, heating it to 900° C. for sintering, and sintering for 6 hours to obtain the copper foil.

[0176] Comparative Example 1

[0177] The method for preparing the copper foil is different from that of the above-mentioned Example 1 in that the dopamine-modified sodium carboxymethyl cellulose is replaced with commonly used sodium carboxymethyl cellulose, and the rest is the same as that of Example 1.

[0178] Comparative Example 2

[0179] The method for preparing the copper foil is different from that of the above-mentioned Example 1 in that the dopamine-modified sodium carboxymethyl cellulose is replaced with a commonly used polyacrylic acid binder K-702, and the rest is the same as that of Example 1.

[0180] [Performance test]

[0181] ① Test the adhesion of copper foil samples:

[0182] Prepare the dried copper foil sample (obtained in step S300), confirm that the surface of the copper foil sample is clean and intact, then fix the copper foil sample, stick the 3M tape to the surface of the copper foil sample, ensure that the tape is smooth and wrinkle-free and the effective bonding length between the tape and the copper foil sample is greater than 5 cm, then use a roller to repeatedly roll the back of the tape 3 times, and finally peel the tape from the surface of the copper foil sample at an angle of 180° at a uniform speed, and observe the surface conditions of the copper foil sample and the tape.

[0183] ② Test the square resistance of copper foil at different temperatures:

[0184] Use a two-probe block resistance tester, place the test bench with pressure monitoring and the probe in a temperature-adjustable test box, when the temperature reaches the set temperature, place a 10*10cm copper foil (obtained in step S400) on the surface of the test bench, press down the probe to make it contact with the copper foil, maintain the pressure at 320~350g, turn on the resistance meter after the pressure and temperature are stable, and read the data after the data is stable.

[0185] The data in Table 1-1 below are obtained.

[0186] Table 1-1 Performance list of embodiments and comparative examples

[0187]

[0188]

[0189] Table 1-2 Content list of examples and comparative examples

[0190]

[0191] From Tables 1-1 and 1-2, it can be seen that the use of ordinary binders cannot meet the requirements of this application. This is because ordinary binders have the disadvantages of low adhesion or poor conductivity after high-temperature carbonization; and by comparing Example 1 and Comparative Example 1, it can be seen that the conductive carbon content formed after sintering of dopamine-modified sodium carboxymethyl cellulose is relatively high.

[0192] Example 2-1

[0193] The preparation method of the copper foil is different from that of Example 1 in that: the PTC raw materials are different. The PTC raw materials of this example (93.8% barium titanate, 0.2% tantalum pentoxide, 6% strontium oxide) are 3 parts; the rest are the same as in Example 1.

[0194] Example 2-2

[0195] The preparation method of the copper foil is different from that of Example 1 in that: the PTC raw materials are different. The PTC raw materials of this example (91.8% barium titanate, 0.2% yttrium trioxide, 8% lanthanum oxide) are 3 parts; the rest are the same as in Example 1.

[0196] Example 2-3

[0197] The preparation method of the copper foil is different from that of Example 1 in that: the PTC raw materials are different. The PTC raw materials of this example (95% barium titanate, 1% antimony trioxide, 4% zirconium titanate) are 3 parts; the rest are the same as in Example 1.

[0198] Comparative Example 3

[0199] The preparation method of the copper foil is different from that of Example 1 in that the PTC raw material is replaced with 100% barium titanate, and the other steps are the same as those of Example 1.

[0200] According to the above performance test method, the data in Table 2-1 are obtained.

[0201] Table 2-1 Performance list of examples and comparative examples

[0202]

[0203] Table 2-2 Content list of examples and comparative examples

[0204]

[0205] It can be seen from Tables 2-1 and 2-2 that the coating prepared by sintering only barium titanate cannot meet the requirements of this application. This is because the Curie temperature of barium titanate after sintering is high, and the resistance of pure barium titanate is high. In addition, the PTC materials formed by sintering different barium titanates and their doped elements have little difference in content.

[0206] Example 3-1

[0207] A method for preparing a copper foil is provided, the method comprising the following steps:

[0208] The mass fractions of the slurry are as follows:

[0209] Calculated by mass, the total number of parts is 100, including:

[0210] PTC raw materials (barium titanate 95.2%, yttrium trioxide 0.8%, barium stannate 4%): 1 part;

[0211] Conductive graphite KS-6: 9 parts;

[0212] Dopamine modified lithium carboxymethyl cellulose: 2 parts;

[0213] Dispersant (BYK22116): 3 parts;

[0214] Cosolvent (ethylene glycol): 3 parts;

[0215] Solvent (deionized water): Remaining parts.

[0216] S100. Provide a slurry for making the above-mentioned conductive layer: add a binder (dopamine-modified lithium carboxymethyl cellulose), a co-solvent (ethylene glycol), and a dispersant (BYK22116) to a solvent (deionized water) and disperse at high speed for 60 minutes at a speed of 300 rpm, then add a PTC raw material and disperse at high speed for 3 hours at a speed of 1000 rpm, finally add a second conductive agent (conductive graphite KS-6), disperse at high speed for 4 hours at a speed of 1000 rpm, discharge the material, place the slurry in a horizontal sand mill, sand grind at 1500 rpm for 3 hours, then discharge the material, and stir at a low speed for degassing to obtain a carbon layer slurry.

[0217] S200, pre-treating the copper substrate: performing corona treatment on the copper substrate;

[0218] S300, coating and drying: coating the slurry on one side of the pretreated copper substrate (thickness of 5 μm), with a single-side coating thickness of 10 μm; then placing the copper foil coated with the slurry in an oven at 130° C. for 6 minutes to obtain a copper foil sample;

[0219] S400, sintering: placing the copper foil sample in an ethane gas atmosphere, heating it to 750° C. for sintering, and sintering for 12 hours to obtain the copper foil.

[0220] Example 3-2

[0221] A method for preparing a copper foil is provided, the method comprising the following steps:

[0222] The mass fractions of the slurry are as follows:

[0223] Calculated by mass, the total number of parts is 100, including:

[0224] PTC raw materials (barium titanate 93.4%, yttrium trioxide 0.6%, barium stannate 6%): 6 parts;

[0225] Conductive graphite KS-6: 4 parts;

[0226] Dopamine modified lithium carboxymethyl cellulose: 5 parts;

[0227] Dispersant (BYK22116): 1 part;

[0228] Cosolvent (ethylene glycol): 10 parts;

[0229] Solvent (deionized water): The remaining parts.

[0230] S100, providing a slurry for making the above-mentioned conductive layer: adding a binder (dopamine-modified lithium carboxymethyl cellulose), a co-solvent (ethylene glycol), and a dispersant (BYK22116) to a solvent (deionized water) for high-speed dispersion for 30 minutes at a rotation speed of 800 rpm, then adding a PTC raw material, dispersing at high speed for 1 hour at a rotation speed of 1500 rpm, and finally adding a second conductive agent (conductive graphite KS-6), dispersing at high speed for 2 hours at a rotation speed of 1500 rpm, discharging the material, placing the slurry in a horizontal sand mill, sand milling at 2200 rpm for 1 hour, then discharging the material, and stirring at a low speed for degassing to prepare a carbon layer slurry.

[0231] S200, pre-treating the copper substrate: performing corona treatment on the copper substrate;

[0232] S300, coating and drying: coating the slurry on one side of the pretreated copper substrate (thickness of 5 μm), with a single-side coating thickness of 5 μm; then placing the copper foil coated with the slurry in an oven at 70° C. for 8 minutes to obtain a copper foil sample;

[0233] S400, sintering: placing the copper foil sample in a methane gas atmosphere, heating it to 850° C. for sintering, and sintering for 8 hours to obtain the copper foil.

[0234] Example 3-3

[0235] A method for preparing a copper foil is provided. The method is different from that in Example 1 in that the sintering temperature is 950°C.

[0236] Comparative Example 4

[0237] A method for preparing a copper foil is provided. The method is different from that in Example 1 in that the sample is not subjected to sintering treatment after being dried.

[0238] According to the above performance test method, the data in Table 3-1 are obtained.

[0239] Table 3-1 Performance list of examples and comparative examples

[0240]

[0241] Table 3-2 Content list of examples and comparative examples

[0242]

[0243] It can be seen from Tables 3-1 and 3-2 that without the sintering process, the prepared coating cannot meet the requirements of this application. This is because barium titanate has a large resistance and is difficult to form a PTC material without sintering.

[0244] In summary, the copper foil provided in the present application has good conductivity within the temperature range of normal battery use. When the battery temperature rises due to an abnormal condition such as a short circuit, the resistance of the copper foil increases rapidly until the circuit is cut off, thereby improving the safety of use.

[0245] The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for a person skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

[0246] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different nouns to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. As mentioned throughout the specification and claims, "including" and "comprising" are open-ended terms, so they should be interpreted as "including / including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application, and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.

[0247] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0248] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0249] The above is only a preferred specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A copper foil, characterized in that: It comprises a copper substrate and a conductive layer located on at least one side of the copper substrate, wherein the conductive layer comprises a PTC material and a conductive agent; The conductive agent includes a first conductive agent, the first conductive agent includes conductive carbon, and the conductive carbon is obtained by reacting any one or more of dopamine-modified carboxymethyl cellulose or a salt thereof.

2. The copper foil according to claim 1, characterized in that: The dopamine-modified carboxymethyl cellulose or its salt includes any one or more of dopamine-modified carboxymethyl cellulose, dopamine-modified carboxymethyl cellulose sodium, dopamine-modified carboxymethyl cellulose potassium, and dopamine-modified carboxymethyl cellulose lithium; The dopamine-modified carboxymethyl cellulose or its salt satisfies any one or more of the following properties: (1) The grafting rate of dopamine in the dopamine-modified carboxymethyl cellulose or its salt is 20% to 30%; (2) The average relative molecular weight of the dopamine-modified carboxymethyl cellulose or its salt is 30,000 to 50,000.

3. The copper foil according to any one of claims 1 to 2, characterized in that: The conductive carbon content in the conductive layer is 5% to 20% by mass.

4. The copper foil according to any one of claims 1 to 2, characterized in that: The conductive layer further includes a second conductive agent, wherein the second conductive agent includes any one or more of carbon black, graphite, carbon nanotubes, and graphene; The mass percentage of the second conductive agent in the conductive layer is 35% to 85%.

5. The copper foil according to any one of claims 1 to 2, characterized in that: The PTC material is obtained by reacting a main material, a first additive and a second additive; The main material includes barium titanate; The first additive includes any one or more of antimony trioxide, yttrium trioxide, and tantalum pentoxide; The second additive includes any one or more of lanthanum oxide, zirconium titanate, strontium oxide, and barium stannate; The mass of the first additive is less than or equal to 1% of the mass of the PTC material; The mass of the second additive is less than or equal to 10% of the mass of the PTC material; The mass percentage of the PTC material in the conductive layer is 10% to 55%.

6. A slurry for making the conductive layer according to any one of claims 1 to 5, characterized in that: The components include: The total number of parts by mass is 100, of which: PTC raw materials: 1 to 6 parts; Second conductive agent: 4 to 9 parts; Binder: 2 to 5 parts; Dispersant: 0.5 to 3 parts; Solvent: 3-10 parts; the rest is deionized water; The binder includes any one or more of dopamine-modified carboxymethyl cellulose or its salt.

7. A method for preparing a copper foil according to any one of claims 1 to 5, characterized in that: The process includes the following: Providing a slurry for preparing the conductive layer: adding 2 to 5 parts of a binder, 3 to 10 parts of a cosolvent and 0.5 to 3 parts of a dispersant into deionized water for a first dispersion, adding 1 to 6 parts of a PTC raw material into the slurry after the first dispersion for a second dispersion, adding 4 to 9 parts of a second conductive agent into the slurry after the second dispersion for a third dispersion, and then sand-milling, stirring and degassing to obtain a slurry; The binder includes any one or more of dopamine-modified carboxymethyl cellulose or its salt; Pre-treating the copper substrate; Coating and drying: coating the slurry on at least one side of the pretreated copper substrate, and drying to obtain a copper foil sample; Sintering: The copper foil sample is placed in a reducing atmosphere and sintered to obtain the copper foil.

8. The preparation method according to claim 7, characterized in that: The sintering temperature is 650°C to 950°C, and the sintering time is 1h to 12h; The reducing atmosphere includes an alkane gas atmosphere.

9. The preparation method according to any one of claims 7 to 8, characterized in that: The first dispersion has a rotation speed of 200 rpm to 800 rpm and a dispersion time of 30 min to 60 min; The second dispersion speed is 1000 rpm to 1500 rpm, and the dispersion time is 1h to 3h; The rotation speed of the third dispersion is 1000 rpm to 1500 rpm, and the dispersion time is 2h to 4h.

10. A current collector for a battery, characterized in that: The invention comprises the copper foil according to any one of claims 1 to 5 or the copper foil prepared by the preparation method according to any one of claims 7 to 9.